Combining an Ecological Experiment and a Genome Scan Show Idiosyncratic Responses to Salinity Stress in Local Populations of a Seaweed - Kinnby, Alexandra; Jonsson, Per R.; Ortega-Martinez, Olga; Töpel, Mats; Pavia, Henrik; Pereyra, Ricardo T.; Johannesson, Kerstin (Frontiers in Marine Science, 2020)
Climate change related effects threaten species worldwide; within species populations may react differently to climate-induced stress due to local adaptation and partial isolation, particularly in areas with steep environmental gradients. Populations of the marine foundation seaweed Fucus vesiculosus are established over a steep salinity gradient at the entrance of the brackish water the Baltic Sea (NE Atlantic). First, we analyzed genetic differentiation among populations using thousands of genetic markers. Second, we measured physiological tolerance to reduced salinity, a predicted effect of climate change in the study area, by measuring growth, phlorotannin (defense compounds) content, and maximum photochemical yield in tissue of the same individuals exposed to both current and projected future salinities. Our results show that despite short geographic distances (max 100 km) most populations were genetically well-separated. Furthermore, populations responded very differently to a salinity decrease of 4 practical salinity units corresponding to projected future salinity. At the high salinity end of the gradient, some populations maintained growth at the cost of reduced phlorotannin production. However, at the low salinity end, mortality increased and growth was strongly reduced in one population, while a second population from similar salinity instead maintained growth and phlorotannin production. Among genetic markers that appeared as outliers (showing more genetic differentiation than the majority of loci) we found that four were associated with genes that were potential candidates for being under selection. One of these, a calcium-binding protein gene, also showed a significant genotype-phenotype relationship in the population where this genetic marker was variable. We concluded that local selection pressure, genetic affinity, and possibly also population history could explain the very different responses to reduced salinity among these populations, despite being from the same geographic area. Our results highlight the importance of local perspective in management of species.